The mitogenomes of Leptographium aureum, Leptographium sp., and Grosmannia fruticeta: expansion by introns - Mukhopadhyay, Jigeesha; Wai, Alvan; Hausner, Georg (Frontiers in Microbiology, 2023)
Introduction Many members of the Ophiostomatales are of economic importance as they are bark-beetle associates and causative agents for blue stain on timber and in some instances contribute towards tree mortality. The taxonomy of these fungi has been challenging due to the convergent evolution of many traits associated with insect dispersal and a limited number of morphological characters that happen to be highly pleomorphic. This study examines the mitochondrial genomes for three members of Leptographium sensu lato [Leptographium aureum (also known as Grosmannia aurea), Grosmannia fruticeta (also known as Leptographium fruticetum), and Leptographium sp. WIN(M)1376)]. Methods Illumina sequencing combined with gene and intron annotations and phylogenetic analysis were performed. Results Sequence analysis showed that gene content and gene synteny are conserved but mitochondrial genome sizes were variable: G. fruticeta at 63,821 bp, Leptographium sp. WIN(M)1376 at 81,823 bp and L. aureum at 104,547 bp. The variation in size is due to the number of introns and intron-associated open reading frames. Phylogenetic analysis of currently available mitochondrial genomes for members of the Ophiostomatales supports currently accepted generic arrangements within this order and specifically supports the separation of members with Leptographium-like conidiophores into two genera, with L. aureum grouping with Leptographium and G. fruticeta aligning with Grosmannia. Discussion Mitochondrial genomes are promising sequences for resolving evolutionary relationships within the Ophiostomatales.